Clinical profile of anemia among 6–60-month children living in South Karnataka – A cross sectional study - Madhusudan, S R; Devi, M Kanchana; Ahuja, Sam; Nagaraj, Niranjan (Indian Journal of Child Health, 2018)
Introduction: Anemia is a worldwide public health problem and has a variable impact on the physical development of child. This study aims to assess the epidemiological characteristics and clinical profile of anemia among 6–60 month children living in South Karnataka. Methods: This was a cross-sectional, community-based study conducted in Bengaluru, from 2012 to 2014. Participants were weighed and measured, and their blood was taken. Demographic, morbidity, and feeding data were obtained from mothers. All the collected data were tabulated and stastically analyzed. Results: Prevalence of anemia in children is 77.8%. Seventy-five children (90%) with anemia belonged to lower socioeconomic status. The chief presenting symptoms in the present study were easy fatigability (34%), loss of appetite (36%), pallor (26), and irritability (24%). The chief clinical signs in anemic children were pallor of mucosa (76%), pallor of skin, palms, and soles (64%), tachycardia (23%), cheilitis (13%), and hemic murmur (9%). Conclusions: Most of the children suffering from anemia were from lower socioeconomic status. Diarrhea was the chief associated symptom in more than half of the cases studied. Hence, the proper periodic deworming measure is advised. Furthermore, timely giving of weaning food, reducing infection by proper immunization, and good personal hygiene will help to prevent anemia.